Leveraging social assistance to strengthen women’s and girls’ climate resilience: What is the potential, and what are promising program designs? - Hidrobo, Melissa; Mueller, Valerie; Bryan, Elizabeth; Nesbitt-Ahmed, Zahrah; Laderach, Peter; Roy, Shalini (International Food Policy Research Institute, 2024)
Climate change is destabilizing agrifood systems globally, disproportionately afflicting rural populations in low- and middle-income countries (LMICs) and leading to escalating food insecurity and disrupted livelihoods. Alongside mitigation efforts, large-scale measures are needed to support climate-vulnerable people. Social assistance (SA) programs – such as cash transfers, in-kind transfers, public works, food assistance for assets programs, and school feeding – are increasingly recognized as promising scalable approaches. Moreover, if properly designed, these programs have the potential to address the disproportionate climate risks that women and girls (WGs) face. WGs have important roles in making agrifood systems more climate-resilient, given that they represent almost 40 percent of the workforce (50 percent in sub-Saharan Africa) (FAO, 2023) and have gender-differentiated roles and knowledge. Yet they are more limited in their opportunities to adapt to climate change, due to systemic inequalities in their access to resources, technologies, information, services, and networks, and due to restrictive social norms.